Peru : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2015)
This paper assesses Peru's fiscal transparency practices in comparison with the IMF's Fiscal Transparency Code, including the new draft pillar on resource revenue management. Peru's practices meet most of the principles of the IMF's Fiscal Transparency Code at good or advanced level. The country provides an extensive set of fiscal information with financial statements covering the entire public sector. There is a comprehensive budget supported by a solid fiscal framework with clear policy objectives embedded in numerical fiscal rules. The country also has a clear and comprehensive legal and fiscal regime for the management of resource revenue.